Case report: Eczematous adverse drug reaction after selpercatinib treatment - Li, Bingrun; Cao, Peng; Xu, Wenjing; Zhang, Litao (Frontiers in Oncology, 2024)
This study reports a 50-year-old patient presented with eczematous drug-eruption induced by selpercatinib after the treatment of non-small cell lung cancer (NSCLC). The patient has symmetric erythematous papules and plaques all over the body with dry, scaly skin accompanied by severe pruritus and visible scarring. After systemic treatment with glucocorticoids, the patient’ skin lesions were reduced well. Currently, the medical literature on the incidence of selpercatinib-induced cutaneous eczematous reactions and their clinical management is scarce. Therefore, this study provides novel evidence for the treatment of selpercatinib-induced cutaneous eczematous reactions.